Proposal of two new genera of the family Zosimeidae Seifried (Copepoda: Harpacticoida): Heterozosime gen. nov. and Acritozosime gen. nov. - Kim, Jong Guk; Lee, Jimin (European Journal of Taxonomy, 2021)
In the Pacific Ocean, the taxonomy of the family Zosimeidae Seifried, 2003 is poorly understood and to date only five species of the genus Zosime Boeck, 1873 are known. During oceanographic cruises exploring the species diversity of harpacticoids, two undescribed zosimeid copepods were sampled from shallow Korean waters and the deep northwestern Pacific. A detailed morphological examination has led us to propose two new genera, Heterozosime gen. nov. for the Korean zosimeid H. tenuis gen. et sp. nov. and Acritozosime gen. nov. for the deep-sea zosimeid A. spinesco gen. et sp. nov. Both new genera exhibit a distinctive feature in that the first thoracic leg has a two-segmented exopod, in contrast to the three-segmented exopod of this leg in all known zosimeid genera. Furthermore, Acritozosime gen. nov. can also be discriminated from other genera by the two-segmented endopod in second to fourth thoracic legs and the reduced setal armatures of the second exopodal segment of antenna, the first endopodal segment of first to third thoracic legs and the third exopodal segment in second to fourth thoracic legs. A comparison of the fundamental structures of appendages suggests that A. spinesco gen. et sp. nov. experienced a unique evolutionary history within the Zosimeidae.